Hypertension in aortic valve disease and its response to valve replacement. Issue 797 (March 1992) - Zezulka, A.; Mackinnon, J.; Beevers, D. G.
Abstract : We have investigated the prevalence of hypertension and the response of blood pressure to operation in 87 patients with lone aortic valve disease who underwent aortic valve replacement. In patients with aortic stenosis alone 26% were hypertensive pre-operatively (age and sex adjusted blood pressure greater than 160 systolic and or greater than 95 mmHg diastolic) and 24% were hypertensive post-operatively. In those with aortic regurgitation alone, hypertension was present in 65% before and 57% after valve replacement using the same criterion. For combined stenosis and regurgitation, the prevalence was 54% and 62%, respectively. The post-operative increase in systolic pressure in patients with aortic stenosis occurred mainly in those with a history of left ventricular failure. In those with aortic regurgitation or combined stenosis with regurgitation, diastolic pressure rose after valve replacement resulting in a prevalence of diastolic hypertension of 44% and 35%, respectively. Blood pressure changes were not predicted by the type of valve inserted nor its size. Our data show that despite severe symptomatic aortic valve disease, systolic hypertension was common in aortic stenosis and diastolic hypertension was found in aortic regurgitation. This underlines the importance of blood pressure monitoring in patients following aortic valve replacement.